(3YbhO GdLeGf aj TYQGA gPG GdReGfs - (3eHGQc Hf CHj HcQ Hf GdTYGQ GdehUdj, CHh GdHQcGJ,J (B654 (3g` s
(3ChdgG (B:s
(3jHJOF HbjUQ Hf YKeGf ef HbjI GdbGa s
(3BNQgG (B:s
(3jfJgi Edi eMeO Hf fUQ Gddg Hf eMeO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B269s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B187 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: (3ai HYV CLRGFgG hHNW jOgs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs